2011
DOI: 10.1088/0953-2048/25/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Reversible effect of strain on transport critical current in Bi2Sr2CaCu2O8 +xsuperconducting wires: a modified descriptive strain model

Abstract: A reversible strain effect on transport critical current I c was found in Bi 2 Sr 2 CaCu 2 O 8+x (Bi-2212) high-temperature superconducting round wires. I c showed unambiguous reversibility at 4 K and 16 T up to an irreversible strain limit of about 0.3 % in longitudinal tension, prompting hope that the Bi-2212 conductor has the potential to sustain mechanical strains generated in high-field magnets. However, I c was not reversible under longitudinal compression and buckling of Bi-2212 grain colonies was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 56 publications
(128 reference statements)
12
64
2
Order By: Relevance
“…In more recent work [52], increased reversibility was observed, and it is suggested that the irreversibility is a result of local stress concentrations around the porosity and voids that plague the present Bi-2212 wires (see Sec. 4), and that the behavior on the plateau is in principle intrinsic and related to strain-induced changes in the field-temperature phase boundary [53], similar to Nb 3 Sn [49], and as recently suggested for YBCO [55][56][57].…”
Section: Superconducting Materials and Conductors: Fabrication And LImentioning
confidence: 85%
See 2 more Smart Citations
“…In more recent work [52], increased reversibility was observed, and it is suggested that the irreversibility is a result of local stress concentrations around the porosity and voids that plague the present Bi-2212 wires (see Sec. 4), and that the behavior on the plateau is in principle intrinsic and related to strain-induced changes in the field-temperature phase boundary [53], similar to Nb 3 Sn [49], and as recently suggested for YBCO [55][56][57].…”
Section: Superconducting Materials and Conductors: Fabrication And LImentioning
confidence: 85%
“…The behavior of superconductors under stress and strain is mainly determined through axial strain experiments on the wires and tapes [49][50][51][52][53][54][55][56][57][58], and through transverse pressure experiments on Rutherford cables [33,[59][60][61][62][63][64][65]. In the sections below we review the main results obtained to date.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cycling within the initial loading range is however quasireversible. More recent data [31], [32] indicate an extended reversible range. It is not clear how much of this behavior is affected by the porosity and connectivity features of early wires.…”
Section: Hts Materials Focusmentioning
confidence: 89%
“…The behavior of Bi-2212 under strain is, in contrast to Nb 3 Sn and YBCO, to a large extent dominated by irreversible reductions in the critical current, which can be attributed to crack formation in the Bi-2212 [52,67]. For many years, the behavior of the I c of Bi-2212 under axial strain could be described according to the following model that was introduced in the mid-1990s [51].…”
Section: Superconducting Materials and Conductors: Fabrication And LImentioning
confidence: 99%